Metode Question dan Answer (Q&A) berbasis LMS pada Mata Kuliah Sejarah Fisika untuk Melatih Keterampilan Berkomunikasi Mahasiswa - Hikmawati Hikmawati; Haerunisyah Sahidu; Kosim Kosim (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2020)
Limited trial research has been conducted on the application of the Question and Answer (Q&A) method based on Learning Management System (LMS) to train students' communication skills. The subjects of this study were 32 students who took the History of Physics lecture in Class 5C for the 2020/2021 Academic Year at the Program Studi Pendidikan Fisika, Universitas Mataram. The instrument used was a student communication skills assessment sheet. The communication skills assessed consist of 3 indicators, namely the ability to answer questions, the ability to communicate ideas with symbols or tables, the ability to work together in groups. Assessment of student communication skills is obtained through observations in the History of Physics lecture activities as many as 7 meetings. The assessment score for each indicator uses a scale of 4. The average value of the ability to answer questions is 3.50 (very good criteria), the ability to communicate ideas with symbols or tables is 3.17 (good criteria), the ability to work together in groups is 3, 42 (good criteria). Thus, the Question and Answer (Q&A) method based on Learning Management System (LMS) can be an alternative learning method for training student communication skills